Occupational ergonomic assessment of hand pain symptoms among Bagh hand block print artisans of the handicraft textile industry in Madhya Pradesh, India. Issue 4 (2nd October 2022) - Kamble, Rajat; Sahu, Avinash; Pandit, Sangeeta
Abstract : Objectives. Hand block printing is a highly repetitive and precision job involving tasks such as hitting the wooden hand block with the hands as a hammer, causing chronic mechanical trauma to the ulnar side of the palm. This study aimed to determine the prevalence of work-related hand symptoms, to identify ergonomic risks and musculoskeletal disorders (MSDs) and evidence of mechanical trauma among artisans working in Bagh print of Madhya Pradesh. Methods. Occupational risk involved in the artisan's wrist area was identified using the modified Dutch musculoskeletal questionnaire (MDMQ) and modified Boston hand evaluation questionnaire. The Boston hand evaluation questionnaire helps in the measurement of the severity of the symptoms. A direct observation study was performed to identify the chronic effects of mechanical trauma (CEMT) on artisan's hands. Results . Symptoms like pain, weakness, numbness and tingling were highly prevalent among the artisans, those with experience <3 years were more likely to report pain during working hours ( p < 0.001) and those with experience >13 years were more likely to report numbness ( p < 0.001) and tingling ( p < 0.001). Conclusion . This study supports the evidence that the new artisans are at higher risks of reporting pain and CEMT, including fever and body pain, ultimately causing job loss.